Optimizing Workplace Accident Prevention During Loading and Unloading on the Mv. Red Rock - Ricky Maulana; Tri Hariyanto; Suharto; Anak Agung Istri Sri Wahyuni (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2026)
Loading and unloading activities on ships are high-risk work activities because they involve heavy equipment, dynamic working conditions, and human factors. The incident that occurred on the MV. Red Rock vessel shows that there are still weaknesses in the implementation of work safety procedures. This study aims to analyze the factors causing work accidents and formulate safety optimization strategies in the loading and unloading process on the MV. Red Rock vessel. This study uses a qualitative descriptive approach carried out during sea practice from August 7, 2024 to August 8, 2025. The study population included ship crew and stevedoring workers (TKBM), while the sample was determined by purposive sampling consisting of the captain, deck officers, crew members, and TKBM. Research instruments included observation sheets, semi-structured interviews, documentation, and field notes. Data analysis used the Miles, Huberman, and Saldaña model through data condensation, data presentation, conclusion drawing, and triangulation. The results of the study indicate that work accidents are caused by low human resource competency, inadequate equipment conditions, and non-compliance with Standard Operating Procedures (SOPs). Furthermore, miscommunication between ship and shore personnel and time pressures increase operational risks, while the implementation of safety meetings, regular equipment inspections, and strict supervision have been shown to improve occupational safety and reduce potential hazards. This study concludes that optimizing occupational safety on the MV Red Rock requires the implementation of integrated SOPs, ongoing training, and strengthened supervision to minimize workplace accidents during the loading and unloading process.